EFEKTIVITAS PENGGUNAAN VIDEO CAMERA DALAM PEMBELAJARAN DAN IMPLIKASINYA TERHADAP PELAYANAN ANAK USIA DINI (USIA 4-6 TAHUN) DI KOTA PADANGNENNY MAHYUDDIN, - MAHYUDDIN, NENNY; SYUKUR, YARMIS; HIDAYATI, ABNA (Program Studi Magister Pendidikan Anak Usia Dini, 2016)
This research was obtained base on the some of phenomenoes in the field that shows service standard of early childhood theacher is not optimum yet because of teacher number is not quite. Due to the fact, there is necessity the solution to increase the service with giving the tool like video camera to record the learning process as a means of supervision for the students. This research head for uncover the effectiveness video camera utilizing in learning and the implication toward earlychilhood service. This research use mixed method which integrating qualitative andquantitative data analysis. Quantitative data was obtain with questionnaire as a main data of the research object and then more explicitly use qualitative data through observation and interview. Research population was PAUD Binaan UNP with sample of PAUD located in the centre and edges of city with the second assumption the place give the different educational service to the studnts. The result show that utilizing video camera proved upgrade learning effectiveness and give the implication toward learning process for early childhood stuent.